Alcohol Misuse and Report of Recent Depression Symptoms among Emergency Department Patients - Bazargan-Hejazi, Shahrzad (Am J Emerg Med, 2008)
OBJECTIVE: This study examines the magnitude of association between alcohol misuse with recent depressive symptoms. METHODS: A cross-sectional study of 412 randomly selected patients ≥18 seeking ED care. RESULTS: 51.0% reported depressive symptoms. At-risk drinking was reported by 26.0% of the sample, 28.2% scored positive for RAPS4. Alcohol abuse, and Binge drinking were reported by 25.1% and 28% of the patients, respectively. According to our results at-risk drinking (OR 2.49; CI 1.47–4.20; P ≤ .001), problem drinking (OR 2.11; CI 1.27–3.51; P ≤ .004), drinking abuse (OR 2.58; CI 1.51–4.40; P < .001), and binge drinking (OR 1.89; CI 1.13–3.15; P < .001) were all related to manifestation of depression symptoms. CONCLUSION: The findings of this study yield information that could be used by emergency department health care practitioners and health educators to educate ED patients at-risk for alcohol misuse and depression.